Understanding the acceptability, barriers and facilitators for chlamydia and gonorrhoea screening in technical colleges: qualitative process evaluation of the "Test n Treat" trial - Charlotte Fleming; Vari M. Drennan; Sarah Kerry-Barnard; Fiona Reid; Elisabeth J. Adams; S. Tariq Sadiq; Rachel Phillips; Wendy Majewska; Emma M. Harding-Esch; Emma C. Cousins; Freya Yoward; Pippa Oakeshott (BMC, 2020)
Abstract Background Low uptake of sexually transmitted infection testing by sexually active young people is a worldwide public health problem. Screening in non-medical settings has been suggested as a method to improve uptake. The "Test n Treat" feasibility trial offered free, on-site rapid chlamydia/gonorrhoea tests with same day treatment for chlamydia (and gonorrhoea treatment at a local clinic,) to sexually active students (median age 17 years) at six technical colleges in London. Despite high rates of chlamydia (6% prevalence), uptake of testing was low (< 15%). In a qualitative study we explored the acceptability, including barriers and facilitators to uptake, of on-site chlamydia screening. Methods In 2016-17 we conducted a qualitative study in the interpretative tradition using face to face or telephone semi-structured interviews with students (n = 26), teaching staff (n = 3) and field researchers (n = 4). Interviews were digitally recorded, transcribed and thematically analysed. Results From the student perspective, feelings of embarrassment and the potential for stigma were deterrents to sexually transmitted infection testing. While the non-medical setting was viewed as mitigating against stigma, for some students volunteering to be screened exposed them to detrimental judgements by their peers. A small financial incentive to be screened was regarded as legitimising volunteering in a non-discrediting way. Staff and researchers confirmed these views. The very low level of knowledge about sexually transmitted infections influenced students to not view themselves as candidates for testing. There were also suggestions that some teenagers considered themselves invulnerable to sexually transmitted infections despite engaging in risky sexual behaviours. Students and researchers reported the strong influence peers had on uptake, or not, of sexually transmitted infection testing. Conclusions This study offers new insights into the acceptability of college-based sexually transmitted infection screening to young, multi-ethnic students. Future studies in similar high risk, hard to reach groups should consider linking testing with education about sexually transmitted infections, offering non stigmatising incentives and engaging peer influencers.